КОМБІНОВАНЕ РЕГУЛЮВАННЯ КОМУТОВАНИМИ КОНДЕНСАТОРАМИ І ВЕНТИЛЬНИМ ПЕРЕТВОРЮВАЧЕМ НАПРУГИ АСИНХРОННОГО ГЕНЕРАТОРА АВТОНОМНО ПРАЦЮЮЧОЇ МІНІ-ГЕС - Мазуренко, Л.І.; Джура, О.В.; Шихненко, М.О. (Інститут електродинаміки Національної академії наук України, 2023)
The principles of operation and a static simulation model of the power-generating equipment of the autonomous power supply source based on a hydroelectric unit with a 275 kVA induction generator and a combined capacitor-inverter excitation system supplying a symmetrical passive load have been developed. The initial excitation of the generator is carried out by a bank of capacitors of the initial excitation. During low power demand the generator voltage is kept constant by adjusting the reactive power of the semiconductor converter, and at high loads, the voltage is adjusted as a result of the switching of additional capacitor banks. The developed methodology for performance analysis the proposed power supply source is based on the IG equivalent circuit. Computations of the static characteristics of the generator operating with a constant rotor speed were carried out and the obtained static characteristics were analyzed for two set values of the load power factor. Ref. 5, table, fig. 4.